FLOOD RUNOFF ANALYSIS IN THE UPPER CHANGJIANG RIVER BASIN - KATO, Hiroyasu; MANO, Akira (PROCEEDINGS OF HYDRAULIC ENGINEERING, 2004)
This study aims to develop a physics-based flood runoff model to reproduce flood peak discharge at few-day duration in continental-scale rivers. Entire global meteorological data set ISLSCP Initiative I and entire global geographic data set GTOPO30 in USGS were used so that this model can be applied for any continental-scale river basin. To express groundwater, two serial tanks were attached to each sub-basin. Runoff intensities from each tank are expressed as a function of physics-based parameters, water depth in the tank, slope, and hydraulic conductivity according to Darcy's law. As a result of applying this model for the Upper Changjiang river basin in 1987 to 1988, this model reproduces the observed daily discharge at Yichang, the upper reach terminal, over the two years in good accuracy.